Effect of heat treatment and osmotic storage on the control of fungi associated with short-lived Inga vera Willd. Embryos - Martins, Rayana; Barbedo, Claudio José; Santos Junior, Nelson Augustos dos (Acta Scientiarum. Biological Sciences, 2025)
Seeds sensitive to desiccation remain metabolically active after dispersion with a high water content, which makes their storage for long periods difficult, due to their deterioration and high proliferation of fungi. One of the ways to maintain or improve the sanitary quality of the seed, preventing the spread and transmission of fungi, is the treatment of these seeds and how they are stored. Thus, Inga vera seeds were subjected to thermotherapy in hot water at different temperatures and submersion periods and to storage in an osmotic polyethylene glycol solution (-2.0 MPa) for 25, 50 and 75 days. They were then evaluated for health (incidence and severity). It was found that osmotic storage was more efficient than heat treatment in reducing the majority of fungi found. The association of both types of treatment produces favorable results and the reapplication of heat treatment can increase fungal control throughout storage. The severity assessment made it possible to detect differences between treatments that were not identifiable in the incidence assessment.